ANALYSIS OF BUSINESS STRATEGY DEVELOPMENT IN CAMPUS INTELLECTUAL PRODUCTS - Rucheni, Rucheni; Mukhsin, Moh; Satyanegara, Diqbal (Universitas Nusa Cendana, 2025)
The Mathematical Labyrinth Board Game is a campus intellectual product in the form of a mathematical equation game. In the use of the product, there are still several things that need to be considered and improved in terms of function, features, and appearance so that it is not yet feasible to be commercialized and its benefits are felt. Thus, the purpose of this study is to investigate potential approaches in making a business plan for the Mathematical Labyrinth Board Game product. The QSPM Matrix and SWOT Analysis method are used in this study as decision-making tools to provide strategies that can be applied to research products. In this case, the IE matrix shows the growth position or growth stage. The weighted average score for IFE is 3.173, while EFE is 3.171. This study produced 7 alternative strategies, including implementing online business strategies and utilizing technology effectively, utilizing and maximizing cooperation with educational institutions, improving management quality, improving product features, improving product image and competitive advantages to have competitiveness, improving product quality, differentiating products appropriately, and managing all resources appropriately and efficiently. Based on the results of the seven (7) strategies, the strategy that is the main priority is implementing an online business strategy and utilizing technology effectively with a TAS (Total Attractive Score) value of 5.936 according to calculations from QSPM. Keywords: Product; Development Strategy; SWOT; QSPM